Uganda Christian University-Mbale University College the Impact of Childlessness on Maried Couples in Akoromit Sub County, Kapelebyong District - Prossy Ajumo (Uganda Christian University, 2024)
The general objective of the study is the impacts of childlessness on married couples in Akoromit Sub County. Having seen that this type of study was not conducted in this area, there was a need to do it as the only way to bridge the gaps amongst couples, like communication gap, integrity /respect and love in families. The amount of pain, emotional trauma and psychological torture that the childless women go through is unquantifiable and immeasurable. Because of the stigmatization of women and the pressure on them they are often driven to consult in darkness spiritualists and native doctors. Some women suffer abuses also at the hands of these spiritualists and native doctors. Some are raped and forced to succumb to various demands of these spiritualists. This study was guided by the following three standard objectives and these are; to explore the causes of childlessness on married couple couples in Akoromit Sub County, to assess the impact of childlessness on married couples who are childless in Akoromit Sub County and to determine the solutions for the families which are childless in Akoromit Sub County? A case study was used for the research design. It was a qualitative approach used for data collection. A sample size of 10 respondents was selected for the discussion. Indeed the impact of childlessness on married couples has affected the lives of people whereby it’s seen that some chose voluntarily not to have children and some involuntarily.
Undergraduate Research